A new method to determine the water activity and the net isosteric heats of sorption for low moisture foods at elevated temperatures. (December 2017) - Tadapaneni, Ravi Kiran; Yang, Ren; Carter, Brady; Tang, Juming
Abstract: In recent years, research studies have shown that the thermal resistance of foodborne pathogens in the low moisture foods is greatly influenced by the water activity (aw ) at temperatures relevant to thermal treatments for pathogen control. Yet, there has been a lack of an effective method for accurate measurement of aw at those temperatures. Thus, the main aim of this study was to evaluate a new method for measuring aw of food samples at elevated temperatures. An improved thermal cell with a relative humidity and temperature sensor was used to measure the aw of the three different food samples, namely, organic wheat flour, almond flour, and non-fat milk powder, over the temperature range between 20 and 80 °C. For a constant moisture content, the aw data was used to estimate the net isosteric heat of sorption ( q st ). The q st values were then used in the Clausius Clapeyron equation (CCE) equation to estimate the moisture sorption isotherm for all test food samples at different temperatures. For all the tested samples of any fixed moisture content, aw value generally increased with the temperature. The energy for sorption decreased with increasing moisture content. With the experimentally determined q st value, CCE describes well about the changes in aw of the food samples between 20 and 80 °C. This study presents a method to obtain aw of a food sample for a specific moisture content at different temperatures which could be extended to obtain q st values for different moisture contents and hence, the moisture sorption isotherm of a food sample at different temperatures. Graphical abstract: Highlights: Water activity (aw ) of the select low moisture foods was determined at 20 to 80 °C. Net isosteric heats of sorption ( q st ) were estimated using the obtained aw values. Effects of temperature on the aw of the food samples were observed. Moisture content (MC) of a food sample exponentially influences the q st . For different MC, the aw data estimated sorption isotherm at different temperatures.